PENGARUH KUALITAS PRODUK DAN DESAIN PRODUK TERHADAP LOYALITAS KONSUMEN - Dini Anggraini (EQUILIBIRIA, 2018)
This study was conducted to determine the condition of the telecommunications industry in the field of business competition intensifies over time, which makes telecommunications companies vying to create marketing strategies that aim to sustain new and achieve a better market share again. As for the problem of this research is "whether the factors of product quality, and product design influence on consumer loyalty to PT. XL Axiata. Tbk Batam branch ". This study to determine whether the factors that influence consumers to consumer loyalty to XL products especially in communities in the region who use XL Batam. The purpose of this study to analyze the effect of each variable, the quality of the product (X1), and product design (X2) on consumer loyalty (Y). In this research, data collection was conducted by questionnaire to 50 respondents XL product users in the Batam region by using a data collection method in this study is a questionnaire, study documentation and interviews. Then conducted data analysis includes testing the validity and reliability, the classical assumption, hypothesis testing by F test and t test analysis and test the coefficient of determination (R2). The data that have met the test of validity, reliability testing, and classical assumption processed to produce a regression equation as follows:Y = 6.008 + 0.333 X1 + 0.222 X2Results of the analysis found that the fourth factor of product quality, and product design has a positive and significant impact on consumer loyalty. Hypothesis testing using t-test showed that the two independent variables studied was shown to significantly affect the dependent variable customer loyalty. Then through the F test can be seen that the variable quality of the product, and significant product design together in customer loyalty. Figures Adjusted R Square of 0.383 indicates that 38.3% variation in customer loyalty could be explained by the two independent variables used in the regression equation. While the remaining 61.7% is explained by other variables outside the two variables used in this study.